Mass Customization and Learner Autonomy: A Mexican Perspective - Llaven Nucamendi, María Elena (Linguistik Online, 2012)
Customization of services or products fundamentally involves choices being made by the cus-tomer. This paper explores the conception of learner autonomy in language learning and its relationship to the capacity of students to make choices about their own education as a pre-requisite for implementing mass customization in learning support. A study of the impedi-ments to learner autonomy in a Mexican context indicates some of the conceptual and cultural issues that should be addressed in implementing mass customization in language learning.